Diel vertical migration of zooplankton at the S1 biogeochemical mooring revealed from acoustic backscattering strength. Issue 2 (1st February 2016) - Inoue, Ryuichiro; Kitamura, Minoru; Fujiki, Tetsuichi
Abstract: We examined the diel vertical migration of zooplankton by using the backscatter strength obtained from moored acoustic Doppler current profilers at mooring site S1 in the North Pacific subtropical gyre. There was seasonal variability in the vertical distribution and migration of the high‐backscatter layers in that they became deeper than the euphotic zone (<100 m) in winter and were confined above this depth in other seasons. Seasonal changes in daylight hours also affected the timing of the diel migration. We found that lunar cycles affected vertical distributions of zooplankton near the surface by changing the light intensity. Physical events, such as mixed‐layer deepening and restratification and the passage of a mesoscale eddy, also affected zooplankton behavior possibly by changing food environment in the euphotic zone. Since the comparison with net samples indicated that the backscatter likely represents the bulk biomass, the accuracy of biomass estimates based on net samples could be influenced by the high temporal variability of zooplankton distributions. Key Points: The diel vertical migration of zooplankton was studied The backscatter strength from the moored ADCP at mooring site S1 was used